Annual Plan of Orissa 1976-77 (Draft) Government of Orissa - Planning Commission (Planning Commission, 1976)
After two decades of planned efforts, Orissa still remains poor and backward. Its per capita income is among the lowest in the States. In 1973-74 it was Rs. 265.6 against Rs. 340.1 for the country as a whole (at 1960-61 prices). the gap between the per capita income of India and Orissa which was 80 rupees in 1950-51 (at 1960-61 prices) rose to 90 rupees in 1970-71. Though the gap has marginally slumped to Rs. 74.5 in 1973-74, Orissa continues to be the third lowest in India in respect of per capita income.
Planning and Co-ordination Department Government of Orissa